Involvement of the oestrogenic receptors in superior mesenteric ganglion on the ovarian steroidogenesis in rat - Vega Orozco, Adriana Soledad (2012)
Oestradiol (E2) is a key hormone in the regulation of reproductive processes. The aims of this work were a) to examine the distributions of oestrogen receptor a (ERa) and ERb in the neurons of the superior mesenteric ganglion (SMG) in the oestrus stage by immunohistochemistry, b) to demonstrate whether E2 in the SMG modifies progesterone (P4), androstenedione (A2) and nitrite release in the ovarian compartment on oestrus day and c) to demonstrate whether E2 in the ganglion modifies the activity and gene expression in the ovary of the steroidogenic enzymes 3b-hydroxysteroid dehydrogenase (3b-HSD) and 20a-hydroxysteroid dehydrogenase (20a-HSD). The ex vivo SMG–ovarian nervous plexus–ovary system was used. E2, tamoxifen (Txf) and E2 plus Txf were added in the ganglion to measure ovarian P4 release, while E2 alone was added to measure ovarian A2 and nitrites release. Immunohistochemistry revealed cytoplasmic ERa immunoreactivity only in the neural somas in the SMG. E2 increased ovarian P4 and A2 release at 15, 30 and 60 min but decreased nitrites. The activity and gene expression of 3b-HSD increased, while the activity and gene expression of 20a-HSD did not show changes with respect to the control. Txf in the ganglion diminished P4 release only at 60 min. E2 plus Txf in the ganglion reverted the effect of E2 alone and the inhibitory effect of Txf. The results of this study demonstrate that ERa activation in the SMG has an impact on ovarian steroidogenesis in rats, thus providing evidence for the critical role of peripheral system neurons in the control of ovarian functions under normal and pathological conditions.